Cyberattacks and State Behaviour - Singh, Ananya; Eberle, Jakub; Weinfurter, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis examines state behavior in response to cyberattacks from a realist perspective with an emphasis on deterrence. It explores the impact of cyberattacks on international relations, alliances, and state interactions. Focusing on the biggest cyberattack in history, NotPetya, as a case study, the research analyzes the strategic use of cyberattacks as tools of state strategies, the complexities of state attribution, the challenges in establishing and enforcing cyber norms, private sector collaboration, inter alia. Insights from interviews with industry experts and practitioners are integrated to bridge the gap between academic theory and real-world practice. The study highlights the evolving nature of cybersecurity strategies, diplomatic maneuvers, the significance of international cooperation, and the complications with clear legal frameworks in cyberspace. This research aims to contribute to a deeper understanding of the dynamics of state behavior in the digital age, offering some insights for policymakers, practitioners, and academics in navigating the complex, ever-growing, and dynamic landscape of global cybersecurity.
Vedoucí práce: Jakub Eberle
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses